2014
DOI: 10.1016/j.jvs.2014.03.278
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular aortic aneurysm repair surveillance may not be necessary for the first 3 years after an initially normal duplex postoperative study

Abstract: These findings suggest that follow-up DU surveillance can be postponed until 3 years after EVAR if the initial result of surveillance DU is normal (no endoleak, sac enlargement, stenosis), with minimal risk of an adverse clinical event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…17,19 Until more data are forthcoming with respect to the revised IFU for the Endologix Powerlink and AFX platforms, the current study strongly suggests that patients treated under the old IFU before 2013 should be restudied annually by CT scan. Studies are now underway investigating post-EVAR surveillance with combined biplane abdominal X-ray and duplex ultrasound imaging to reduce long-term radiation and contrast exposure.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…17,19 Until more data are forthcoming with respect to the revised IFU for the Endologix Powerlink and AFX platforms, the current study strongly suggests that patients treated under the old IFU before 2013 should be restudied annually by CT scan. Studies are now underway investigating post-EVAR surveillance with combined biplane abdominal X-ray and duplex ultrasound imaging to reduce long-term radiation and contrast exposure.…”
Section: Discussionmentioning
confidence: 91%
“…The 2.4% incidence of type IIIa endoleaks reported here is comparable to that of recent studies using Endologix and other modular endografts, which found a 2% to 2.7% long-term incidence of type III endoleaks across multiple endograft platforms. 14,17 In a recent detailed analysis of 108 patients treated with Endologix AFX endograft, Welborn et al 18 reported a 2.3% incidence of type IIIa endoleaks. In addition, independent core laboratory data extracted from two recently presented, but as yet unpublished studies, of the Endologix AFX system by Motaganahalli et al and Arthurs et al found four type IIIa endoleaks in 127 combined patients (3.1%) monitored an average of 10 months after elective EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a 2.4% long-term incidence of type IIIa endoleak which is comparable to other smaller reports over various EVAR platforms. 7,8 However, the incidence of those experiencing modular migration without endoleak remained unclear. 9 Additionally, the true incidence of clinically significant type IIIa endoleaks may be much higher.…”
Section: Discussionmentioning
confidence: 99%
“…1 Of those who undergo EVAR, 13% to 22% will require reintervention. 2,3 A short infrarenal neck, neck angulation of >45°, and large aortic neck (>28 mm) are predictors of reintervention, 4,5 and large aneurysms (>6.5 cm diameter) and postdeployment migration are poor prognostic signs and associated with increased rates of aneurysm-related morbidity. 6,7 Thus, certain subsets of patients would particularly benefit from effective post-EVAR surveillance, and it is our contention that patients with HN anatomy, defined by neck length of <10 mm, neck angle of 60°, ≥50% circumferential proximal neck thrombus (≥2 mm thick), ≥50% circumferential calcified proximal neck, reverse taper, or a diameter >31 mm, should strictly adhere to surveillance protocols.…”
Section: Discussionmentioning
confidence: 99%
“…1 Of patients who undergo EVAR, 13% to 22% require reintervention. 2,3 Several studies have compared different aspects of aortic neck morphology as a predictor of outcome after EVAR. Aortic neck angulation of >45°, a short infrarenal neck, a large aortic neck, and large aneurysms (>6.5 cm in diameter) are predictors of reintervention 4,5 and associated with increased rates of aneurysm-related morbidity.…”
mentioning
confidence: 99%